2022
DOI: 10.1017/jfm.2022.314
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced vibrations of a D-section prism at a low Reynolds number

Abstract: This paper presents the response and the wake modes of a freely vibrating D-section prism with varying angles of attack ( $\alpha = 0^\circ \text {--}180^\circ$ ) and reduced velocity ( $U^* = 2\text {--}20$ ) by a numerical investigation. The Reynolds number, based on the effective diameter, is fixed at 100. The vibration of the prism is allowed only in the transverse direction. We found six types of response with increasing angle of attack: typical vortex-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
53
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 80 publications
(200 reference statements)
14
53
2
Order By: Relevance
“…For instance, unlike the FIV response of a circular cylinder that will transfer into desynchronization after the lock-in range with increasing inflow velocity, the FIV response of a square cylinder will involve galloping instability (Zhao 2015;Zhao et al 2019). Past experimental and numerical results also indicated that the attack angle (or, direction of the incoming flow) of the elastically mounted bluff body will significantly affect the accompanied structural stability situation (Zhao et al 2014;Seyed-Aghazadeh, Carlson & Modarres-Sadeghi 2017;Chen et al 2022). In terms of the FIV response of an asymmetrical bluff body, Zhao, Hourigan & Thompson (2018) experimentally investigated the dynamic response (including lock-in and galloping) of the flow past an elastically mounted forward-or backward-facing D section.…”
Section: Geometrical Effect On Gallopingmentioning
confidence: 99%
See 4 more Smart Citations
“…For instance, unlike the FIV response of a circular cylinder that will transfer into desynchronization after the lock-in range with increasing inflow velocity, the FIV response of a square cylinder will involve galloping instability (Zhao 2015;Zhao et al 2019). Past experimental and numerical results also indicated that the attack angle (or, direction of the incoming flow) of the elastically mounted bluff body will significantly affect the accompanied structural stability situation (Zhao et al 2014;Seyed-Aghazadeh, Carlson & Modarres-Sadeghi 2017;Chen et al 2022). In terms of the FIV response of an asymmetrical bluff body, Zhao, Hourigan & Thompson (2018) experimentally investigated the dynamic response (including lock-in and galloping) of the flow past an elastically mounted forward-or backward-facing D section.…”
Section: Geometrical Effect On Gallopingmentioning
confidence: 99%
“…This study (Zhao et al 2018) also applied Den Hartog's stability criterion (Den Hartog 1956) (discussed later herein) in order to explain the differences in response caused by the different facing orientations of the obstacle in the flow. Chen et al (2022) conducted the numerical investigation of a FIV system consisting of a D-section prism with varied attack angles at a low Reynolds number. The presented results were generally similar to those of Zhao et al (2018) and displayed a more detailed response differentiation with reference to the variations of maximum amplitude envelope at different angles of attack.…”
Section: Geometrical Effect On Gallopingmentioning
confidence: 99%
See 3 more Smart Citations